House of Refuge Origins of Juvenile Reform in New York State, 1815-1857 - Pickett, Robert (Syracuse University Press, 1969)
The New York House of Refuge, the first institution in America to deal with the juvenile delinquent as a special problem, opened its doors in 1825. Deeply concerned with the plight of the thousands of children who roamed the New York City streets, many of them becoming professional criminals, a volunteer group called the Society for the Reformation of Juvenile Delinquents, founded the institution to rehabilitate "deviant" adolescents. This is the story of the critical early years of juvenile reform, which soon became a national movement. Current reform concepts are discussed in the Introduction and related to their seventeenth century origins, thus setting the stage for the 1825 world scene that gave rise to the Refuge idea. The following chapters trace events from their European background through the first administration of the House of Refuge, relating Refuge history to the changing character of penal institutions. No one knew how to turn delinquents into virtuous, industrious citizens. Trial and error approaches to solving the problem were often thwarted by the founders themselves, but some methods did prove successful. The personalities of the institution's administrators and of their youthful charges come to life through diary and journal accounts kept by the leading characters in this description of one historic attempt at "taming of the deviant." The House of Refuge finally closed in 1935, replaced by other institutions, but, as the author points out, problems remain today. The epilogue provides a broad sketch of the importance of the House of Refuge to current reform developments and present-day problems of juvenile delinquency. Extensive documentary information and occasional sidelights on the historical events under discussion can be found in the notes. Five tables present a sampling of 500 inmates of the House of Refuge, analyzed by ethnic origins, living arrangements, and family composition.